Réseaux écologiques dans l’Arc alpin - Yann Kohler; Thomas Scheurer; Aurelia Ullrich (Revue de Géographie Alpine)
In response to decreasing biodiversity and new phenomena such as climate change, the number of initiatives aimed at creating ecological networks is increasing. Research and activities based on the theme of ecological connectivity are generating a completely new perception of methods of protecting the natural environment: there is a shift from a conservationist approach to natural systems to one that is more functional. The place and role of protected areas within their regions are being redefined. Such areas are now situated in a wider territorial context and new cooperative arrangements are encouraged with local actors. The alpine approach adopted in establishing a transalpine ecological network, illustrated by several examples, underlines the importance of both an international framework for such activities and the need to extend them to include not only the classic actors in the protection of the natural environment, but also other sectors that until now have seldom been involved.